Distinct In Vitro T-Helper 17 Differentiation Capacity of Peripheral Naive T Cells in Rheumatoid and Psoriatic Arthritis - Baricza, Eszter; Marton, Nikolett; Királyhidi, Panna; Kovács, Orsolya Tünde; Kovácsné Székely, Ilona; Lajkó, Eszter; Kőhidai, Lászó; Rojkovich, Bernadett; Érsek, Barbara; Buzás, Edit Irén; Nagy, György (Frontiers in Immunology, 2018)
Background The T-helper 17 (Th17) cells have a prominent role in inflammation as well as in bone and join destruction in both rheumatoid and psoriatic arthritis (RA and PsA). Here, we studied Th17 cell differentiation in RA and PsA. Methods Blood samples from healthy donors, RA and PsA patients were collected. CD45RO− (naive) and CD45RO+ (memory) T cells were isolated from peripherial blood mononuclear cell by magnetic separation. Naive T cells were stimulated with anti-CD3, anti-CD28, and goat anti-mouse IgG antibodies and treated with transforming grow factor beta, interleukin (IL)-6, IL-1β, and IL-23 cytokines and also with anti-IL-4 antibody. IL-17A and IL-22 production were measured by enzyme linked immunosorbent assay, RORC, and T-box 21 (TBX21) expression were analyzed by quantitative polymerase chain reaction and flow cytometry. C-C chemokine receptor 6 (CCR6), CCR4, and C-X-C motif chemokine receptor 3 expression were determined by flow cytometry. Cell viability was monitored by impedance-based cell analyzer (CASY-TT). Results RORC, TBX21, CCR6, and CCR4 expression of memory T cells of healthy individuals (but not RA or PsA patients) were increased (p < 0.01; p < 0.001; p < 0.05; p < 0.05, respectively) compared to the naive cells. Cytokine-induced IL-17A production was different in both RA and PsA patients when compared to healthy donors (p = 0.0000026 and p = 0.0001047, respectively). By contrast, significant differences in IL-22 production were observed only between RA versus healthy or RA versus PsA patients (p = 0.000006; p = 0.0013454, respectively), but not between healthy donors versus PsA patients. Conclusion The naive CD4 T-lymphocytes are predisposed to differentiate into Th17 cells and the in vitro Th17 cell differentiation is profoundly altered in both RA and PsA.